1989
DOI: 10.1128/jb.171.6.2956-2962.1989
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of p-cresol mediated by a partially purified methylhydroxylase from a denitrifying bacterium

Abstract: Anoxic cell extracts of a denitrifying bacterial isolate were shown to oxidize p-cresol to phydroxybenzoate. Oxidation of the substrate was independent of molecular oxygen and required nitrate as the natural terminal electron acceptor. Two enzyme activities were implicated in the pathway utilized by PC-07. A p-cresol methylhydroxylase mediated the oxidation ofp-cresol to p-hydroxybenzaldehyde, which was further oxidized to p-hydroxybenzoate by an NAD+-dependent dehydrogenase. The PC-07 methylhydroxylase was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…1. This confirms the suggestion of Bossert et al (2) from the oxidized-reduced difference spectrum of the partially purified enzyme that it contained heme and flavin moieties. The ratio of 0.9 of the peak at 275 nm to that at 416 nm for the reduced enzyme is slightly lower than that for the similar enzyme from P. putida NCIB 9869.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…1. This confirms the suggestion of Bossert et al (2) from the oxidized-reduced difference spectrum of the partially purified enzyme that it contained heme and flavin moieties. The ratio of 0.9 of the peak at 275 nm to that at 416 nm for the reduced enzyme is slightly lower than that for the similar enzyme from P. putida NCIB 9869.…”
Section: Resultssupporting
confidence: 81%
“…Partial purification of the enzyme suggested that it was of a type similar to that from the Pseudomonas sp., containing flavin and cytochrome, although this description was considered preliminary until spectra of the purified enzyme were obtained (2). This is now confirmed here by the complete purification of the enzyme and characterization of its subunit structure.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Methyl groups are removed to leave hydroxyl substituents. The anaerobic degradation of many industrially produced phenolics, including phenol and p-cresol (4-methylphenol), converge at the level of 4-HBA, which is also a common growth substrate for different anaerobic bacteria (38). The peripheral pathway for the anaerobic degradation of 4-HBA involves two catabolic steps, i.e., its CoA-dependent activation and further reductive dehydroxylation to benzoyl-CoA ( Fig.…”
Section: Gene Clusters For Degradation Of Aromatic Acidsmentioning
confidence: 99%